Measuring international capital movements - Michael, Walther P. (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1971)
The purpose of the study carried out in this book is to construct integrated accounts of international capital flows, including grants, between individual countries by type of capital. The basic data on capital movements are the balance of payments data reported to and published by the International Monetary Fund.
Includes index
Includes bibliographical references.
usc 21/05/18
Loans
Keywords: Investments, Foreign; International finance